Electrochemical Evidences for the Enhancement of Heterogeneous Electron Transfer Rates of Riboflavin in the Presence of Copper (Dhaka University Journal of Science, 2015)
Evidences for the enhancement of the heterogeneous electron transfer rates of riboflavin in the presence of copper in aqueous medium with a glassy carbon electrode were investigated by cyclic voltammetry, chronocoulometry and differential anodic stripping pulse voltammetry. It was found that copper exhibits a multi-nuclear complex with riboflavin in aqueous KCl solution. The overall stability constant of the complex was calculated (log? = 11.17), which is in a good agreement for the formation of a stable copper-riboflavin complex. DOI: http://dx.doi.org/10.3329/dujs.v62i2.21980 Dhaka Univ. J. Sci. 62(2): 147-152, 2014 (July)